International co-operation of law enforcement bodies of states in the sphere of ensuring economic security - Аракелян, Мінас Рамзесович; Аракелян, М. Р.; Arakelian, Minas R.; Бехруз, Хашматулла Набієвич; Бехруз, Х. Н.; Behruz, Hashmatulla; Бірюков, Руслан Миколайович; Бірюков, Р. М.; Biriukov, Ruslan M. (Riga: Baltija Publishing, 2025)
The subject of the present study is the conceptual, theoretical and methodological research of international co-operation of law enforcement bodies of states in the sphere of ensuring economic security, primarily at the international level and on the regional European level. Methodology. The paper employs a range of general scientific and special legal methods. In this particular context, the method of analysis and synthesis is of critical importance in order to evaluate the methods and parameters of co-operation between police bodies. The historical method was utilised to trace the emergence and development of the legal and institutional foundations and principles of international co-operation of law enforcement bodies in ensuring economic security of states. The comparative method proved to be of great significance in the course of research into the activities of international law enforcement co-operation bodies and domestic bodies of states. The objective of this article is to formulate a cohesive methodology for comprehending the collaborative efforts of law enforcement entities in safeguarding the economic interests of nations. The findings of the study demonstrate that the comprehensive enhancement of law enforcement co-operation among states to ensure economic security is firmly grounded in international treaty law and is effectively institutionalised. Concurrently, the advent of contemporary challenges is concomitant with the rise of criminal networks that exercise control through the utilisation of advanced technologies. This situation necessitates a concerted international response, whereby developed states are obligated to provide assistance to their developing counterparts. Conclusion. The article concludes that the extant legal and institutional frameworks of international co-operation of law enforcement bodies in ensuring economic security of states can be further developed through enhanced co-operation in information sharing, exchange of best practices and training of legal professionals. Furthermore, academic co-operation is of paramount importance for the continued development of new approaches towards the co-operation of law enforcement agencies in ensuring the economic security of states.
Arakelian M. International co-operation of law enforcement bodies of states in the sphere of ensuring economic security / M. Arakelian, H. Behruz, R. Biriukov // Baltic Journal of Economic Studies. – Riga: Baltija Publishing, 2025. – 11(2). - Р. 104–111. URL: https://doi.org/10.30525/2256-0742/2025-11-2-104-111
Keywords: international economic security; state economic security; Interpol; Europol; economic crime; crime prevention; international co-operation in the prevention and combatting crime